Dehydroepiandrosterone anti-atherogenesis effect is not via its conversion to estrogen - Cheng Heng-hui; Hu Xiao-jing; Ruan Qiu-rong (Acta Pharmacologica Sinica, 2016)
Aim: This study was conducted to demonstrate the anti-atherosclerotic effect of dehydroepiandrosterone (DHEA) and to investigate its possible mechanisms and whether this effect is related to its conversion to estrogen. Methods: Forty male New Zealand White rabbits aged 3 months were divided into 5 groups (n=8 per group) and fed different diets for 10 weeks. Serum lipid levels, the area of atherosclerotic lesions and the mRNA levels of monocyte chemoattractant protein-1 (MCP-1) and vascular cell adhesion molecule-1 (VCAM-1) in aortic lesions were measured. Then cultured vascular smooth muscle cells (VSMCs) stimulated by oxidized low density lipoprotein-cholesterol (ox-LDL) were treated by DHEA. The gene and protein expression levels of MCP-1 and VCAM-1 in VSMCs was detected. The plasmid with or without the gene of cytochrome P450 aromatase (CYP19) was transient transfected into cultured VSMCs respectively. Twenty hours later, the cells were stimulated with ox-LDL and DHEA. Results: DHEA could obviously decrease the area of atherosclerotic lesions and the expressions of MCP-1 and VCAM-1 in aortic lesions. But all-trans retinoic acid (atRA) which was reported would limit restenosis after balloon angioplasty had no visible synergistic effect with DHEA. DHEA could also reduce ox-LDL-induced MCP-1 and VCAM-1 expression in untransfected or transfected VSMCs. Conclusion: The anti-atherosclerotic effect of DHEA had nothing to do with the catalysis of cytochrome P450 aromatase (CYP19), or was not related to its conversion to estrogen.